Survei foto sebagai komunikasi warna gigi tiruan cekat di jakarta - James Handojo; Jacqueline Jacqueline (Fakultas Kedokteran Gigi Universitas Trisakti, 2023)
Background: Clear and effective communication between dentists and technicians is a requirement for getting the right color and obtaining a good prosthesis. Purpose: To find out the procedure for selecting and communicating the color of fixed prosthesis performed by dentists in Jakarta. Methods: This research method is a descriptive observational study with a cross-sectional design with 96 respondents. The data was collected through a questionnaire addressed to Jakarta-based dentists, and the data was then displayed in the form of a column and percentage. Results: Dentists who rarely do not include dental photos by 31%. Dentists who never include low-quality photos by 36%. Dentists often include high-quality photos by 45%. Conclusion: Dentists who often include high-quality photos are 45%, and dentists who often don’t include photos in communicating with dental technicians are 17%. The results of this study indicate that more dentists send photos in communicating with dental technicians.